Nikoulabasis roseosticta, sp. nov. from Fiji (Odonata: Coenagrionidae) - Beatty, Christopher D.; Rashni, Bindiya; Cordero-Rivera, Adolfo; Marinov, Milen (Zootaxa, 2023)
Nikoulabasis roseosticta sp. nov. (holotype ♂, Fiji, Vanua Levu Island, Navuturerega creek, 6 August 2009, Christopher Beatty leg.) is erected as a new taxon. Illustrations of key characters and a distribution map are provided.